Quantitative prediction of optical static refractive index in complex oxides - Lan Yang; Xiao Zhou; Xudong Ni; Li Huang; Lianduan Zeng; Zhongyang Wang; Jun Song; Tongxiang Fan (npj Computational Materials)
Abstract The optical static refractive index, a critical intrinsic property of materials, plays a vital role in advanced optoelectronic applications. Accurate prediction of this index is essential for the efficient design and optimization of materials with tailored optical properties. Here, we present a robust predictive model that accurately forecasts the optical static refractive indices of complex oxides across diverse crystal structures and compositions. By leveraging chemical bond theory, our model elucidates the influence of intrinsic physical properties, including chemical bonds and d-electron bands, on the refractive index. Through rigorous analysis of 41 complex oxide systems and 5 doped systems, we demonstrate that our predictions align closely with experimental data, showcasing the model’s high accuracy and broad applicability. This work not only accelerates the development of novel materials and spectral design but also provides profound physical insights for optimizing and customizing optical properties.